THE IMPLEMENTATION OF BLOCKCHAIN SYSTEM IN VEHICLE REGISTRATION CERTIFICATE (BPKB) DATA BASED ON A WEBSITE - Samola, Jonathan; Tenda, Edwin; Pinontoan, Benny; Ketaren, Eliasta (Jurnal TIMES, 2024)
The Vehicle Registration Certificate (STNK) and the Vehicle Ownership Document (BPKB) are crucial documents for identifying and proving vehicle ownership. Without a BPKB, verifying the legitimacy of a vehicle becomes difficult, potentially rendering it illegal and increasing the risk of it being classified as stolen. The process of verifying a BPKB at the central office involves lengthy and time-consuming procedures, complicating the process. The lack of efficient methods for verifying vehicle documents can lead to the production of counterfeit documents by unauthorized parties. This research proposes the development of a secure and easily traceable web application utilizing Ethereum blockchain technology. The application employs Ethereum blockchain architecture and MetaMask as a digital wallet for transactions and login, along with JavaScript, HTML, and CSS for the front end. This solution aims to streamline the verification process, enhance document security, and prevent the circulation of fraudulent vehicle documents. With this system, vehicle document verification becomes faster and more efficient. Blockchain ensures that every transaction and document is securely recorded and immutable, reducing the risk of forgery. MetaMask provides additional security, while modern web technologies ensure the application is user-friendly. This solution strengthens vehicle document security and simplifies the verification process.